Effect of a stepwise opioid-sparing analgesic protocol on in-hospital oxycodone use and discharge prescription after cesarean delivery. Issue 2 (10th November 2020) - Landau, Ruth; Romanelli, Erik; Daoud, Bahaa; Shatil, Ben; Zheng, Xiwen; Corradini, Beatrice; Aubey, Janice; Wu, Caroline; Ha, Catherine; Guglielminotti, Jean
Abstract : Introduction: Opioid exposure during hospitalization for cesarean delivery increases the risk of new persistent opioid use. We studied the effectiveness of stepwise multimodal opioid-sparing analgesia in reducing oxycodone use during cesarean delivery hospitalization and prescriptions at discharge. Methods: This retrospective cohort study analyzed electronic health records of consecutive cesarean delivery cases in four academic hospitals in a large metropolitan area, before and after implementation of a stepwise multimodal opioid-sparing analgesic computerized order set coupled with provider education. The primary outcome was the proportion of women not using any oxycodone during in-hospital stay ('non-oxycodone user'). In-hospital secondary outcomes were: (1) total in-hospital oxycodone dose among users, and (2) time to first oxycodone pill. Discharge secondary outcomes were: (1) proportion of oxycodone-free discharge prescription, and (2) number of oxycodone pills prescribed. Results: The intervention was associated with a significant increase in the proportion of non-oxycodone users from 15% to 32% (17% difference; 95% CI 10 to 25), a decrease in total in-hospital oxycodone dose among users, and no change in the time to first oxycodone dose. The adjusted OR for being a non-oxycodone user associated with the intervention was 2.67 (95% CI 2.12 to 3.50). With the intervention, the proportion of oxycodone-free discharge prescription increased from 4.4% to 8.5% (4.1% difference; 95% CI 2.5 to 5.6) and the number of prescribed oxycodone pills decreased from 30 to 18 (−12 pills difference; 95% CI −11 to −13). Conclusions: Multimodal stepwise analgesia after cesarean delivery increases the proportion of oxycodone-free women during in-hospital stay and at discharge.